2019
DOI: 10.1021/acs.iecr.9b05051
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Energy Savings from Simultaneous Triple Esterification of C4C6 Alcohols in a Single Reactive Distillation Column

Abstract: This paper introduces multiple esterification reactions of three alcohols occurring in a single reactive distillation (RD) column and reports significant energy savings by combining three reactions in the single unit. To realize a feasible integration of the three reactions, the removal of the common water product from the unstable heterogeneous azeotrope should be possible through liquid–liquid decantation in the eight-component system. For this multireaction system, only the direct sequence can produce three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The examined double-feed column satisfies the requirement for an adequate level of reaction. Furthermore, the liquid composition (x 4 ) is located within the reachable region, x 4 : [16,11,5], which verifies the feasibility of the design. Notably, the feasibility evaluation including stage calculations of the RD column required approximately 3.01 s, implying the potential for conducting a timely feasibility evaluation for double-feed columns.…”
Section: Azeotropic Mixtures With An Infinite Reaction Difference Pointsupporting
confidence: 53%
See 1 more Smart Citation
“…The examined double-feed column satisfies the requirement for an adequate level of reaction. Furthermore, the liquid composition (x 4 ) is located within the reachable region, x 4 : [16,11,5], which verifies the feasibility of the design. Notably, the feasibility evaluation including stage calculations of the RD column required approximately 3.01 s, implying the potential for conducting a timely feasibility evaluation for double-feed columns.…”
Section: Azeotropic Mixtures With An Infinite Reaction Difference Pointsupporting
confidence: 53%
“…Reactive distillation (RD) is a promising intensification technique that integrates chemical reactions and separation into a single column filled with a catalyst, enabling the simultaneous removal of products and achieving high reaction conversion and yield by overcoming the equilibrium limit. , RD is an attractive approach for decreasing the energy consumption of distillation alone . The practical applications of RD have demonstrated a significant reduction of 30 to 50% in capital costs and energy consumption compared to conventional processes with the risk of gas emissions mitigated. , The advantages of RD have led to numerous industrial implementations of etherification (e.g., methyl tert -butyl ether, ethyl tert -butyl ether, and tert -amyl methyl ether), , esterification (e.g., n -butyl acetate, n -amyl acetate, n -hexyl acetate, and cyclohexyl acetate), transesterification (e.g., dimethyl carbonate, diethyl carbonate, and propylene glycol methyl ether acetate), and olefin metathesis (e.g., 2-pentene) with a variety of studies conducted to improve the energy efficiency of the reaction and separation systems . While RD offers significant advantages over conventional processes, it is important to note that its benefits may not always be applicable, which means an RD column is sometimes not beneficial in the infeasible integration of reaction and separation, and the reaction would impact the presence of separation boundaries. , Consequently, the feasibility of an RD column should be assessed under the given specifications to determine the suitability of implementing RD.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive distillation (RD) is an efficient process intensification technology that can break the reaction equilibrium limit, shorten the processing time, and reduce the cost . Esterification is one of the most extensive applications of RD, which has successfully realized the production of methyl acetate, n -butyl acetate, and other esters, and has also been reported in the production of n -butyl acrylate. , Moraru and Bildea confirmed that reactive distillation technology can be used to produce high-purity n -butyl acrylate products through process simulation. The pilot test and modeling analysis of Schwarzer and Hoffmann showed that the ester fraction in a single reactive distillation column can reach 0.93, which proves that RD can be quite feasible in the production of BA.…”
Section: Introductionmentioning
confidence: 96%
“…In azeotropic distillation, the presence of an azeotrope causes the formation of distillation boundaries or separatrix in the multiple components, 8 and these boundaries cannot be circumvented by simple distillation 9 . This thermodynamic hurdle can be overcome by azeotropic distillation with an immiscible component forming the azeotrope, 10,11 extractive distillation with an entrainer, 12,13 and even reactive distillation by combining reaction and distillation 14,15 . In addition, pressure‐swing distillation (PSD) can efficiently separate azeotropic mixtures without the use of extra components and is environmentally friendly 16 .…”
Section: Introductionmentioning
confidence: 99%